MODEL PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Sri Subarinah (Universitas Negeri Yogyakarta, 2007)
Abstract This research has been carried out to improve the mathematics learning activity and by Realistic Mathematic Education (RME). This research was done in three cycles to the fourth grade students of the State Elementary School 27 in Ampenan in the academic year of 2006/2007. The result shows that to improve the learning activity, the implementation of RME should involve the following step: (1) the instruction has to begin with arousing motivation and apperception, (2) the students solve contextual problems with a very limited or without the teacher’s help, (3) the teacher presents the essential concept following the solution of the contextual problem, (4) the result of the students discussion has to be presented in front of the class by the students, and (5) the final step of the instruction has to be the making summary and giving homework assignment. Keywords: RME, learning activity, and learning achievement